Electro-dewatering of dredged sediments by combined effects of mechanical and electrical processes: Influence of operating conditions. (1st September 2020) - Ammami, M.T.; Song, Y.; Benamar, A.; Portet-Koltalo, F.; Wang, H.
Abstract: The maintenance of harbor waterways generates large amounts of dredged sediments which can be contaminated. These sediments are inappropriate for disposal at sea and are generally stored in coastal on-land disposal sites. But fine-grained sediments involve very high moisture content and very low hydraulic conductivity, which cause natural or mechanical consolidation very difficult to occur. Removing water from contaminated dredged sediments in disposal facilities is crucial to save storage space because water removal can drastically reduce the disposal volume, allow material stabilization and can contribute to eliminate soluble contaminants. In this research dredged fine marine sediments collected from a storage site facility were used to investigate the effects of pressure processing and an electric potential gradient on a combined electro-dewatering (EDW) process. In order to evaluate the impact of each operating factor and their interaction, a Box-Benhken experimental design was applied. Experiments were carried out on a laboratory designed filtration/loading cell, submitted to different potential gradients (0.5–1.5 V/cm) and pressure (50–200 kPa). Mathematical modeling of the responses (water removal and sediment settlement) have been performed. The results demonstrated that the combination of the two force fields significantly improved the dewatering process and accelerated sediments consolidation, which is beneficial for their storage or further civil engineering applications. Both force fields contributed by the similar way to the water removal. In contrast, results indicated that the effect of the applied pressure was more effective for enhancing sediment settlement compared to voltage gradient. The aqueous effluents containing high amounts of ionic and reduced species in alkaline condition, did not allowed the quantitative elimination of heavy metals.